+0  
 
+1
45
1
avatar+21 

\(\frac{2x + 3}{x - 4} - \frac{2x - 8}{2x + 1} = 1\)

 

Solve for x.

 Dec 30, 2019

Best Answer 

 #1
avatar+98 
+3

Multiply both sides by (x-4)(2x+1)

then we get (2x + 3)(2x + 1) - (2x - 8)(x - 4) = (x - 4)(2x + 1)

Simplifies to 31x - 25 = 0

so x=25/31

 Dec 30, 2019
 #1
avatar+98 
+3
Best Answer

Multiply both sides by (x-4)(2x+1)

then we get (2x + 3)(2x + 1) - (2x - 8)(x - 4) = (x - 4)(2x + 1)

Simplifies to 31x - 25 = 0

so x=25/31

Atroshus Dec 30, 2019

13 Online Users

avatar